f(1) = 3x² + 6x-9
ajudar !!!
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo a passo:
Nesse caso é só substituir x por 1
f(1) = 3x² + 6x - 9
f(1) = 3*1² + 6*1 - 9
f(1) = 3*1 + 6*1 - 9
f(1) = 3 + 6 - 9
f(1) = 9 - 9
f(1) = 0
Respondido por
1
Vamos là.
f(x) = 3x² + 6x - 9
f(1) = 3 + 6 - 9 = 0
Perguntas interessantes
Filosofia,
7 meses atrás
Ed. Física,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
História,
1 ano atrás